Identification of Anaerobic Bacteria in Iranian patients with Rheumatoid Arthritis - Shafeian, Shahb; Bandehpour, Mojgan; Mirzaahmadi, Sina; Tofighi, Azadeh (Novelty in Biomedicine, 2013)
Please cite this article as: Shafeian SH, Bandehpour M, Mirzaahmadi S, Tofighi A. Identification of Anaerobic Bacteria in patients with Rheumatoid Arthritis. . Novel Biomed 2013;1(2):39-42. Background: There is a report about the 2-5% prevalence for septic arthritis by anaerobic bacteria. The relevance between synivitis and intestinal microbial flora has been a hypothesis for ten years. The PCR with sensitivity and specificity 99% for microorganism detection in acute, chronic and relapse form of septic arthritis is helpful. Methods: In this research we designed to diagnosis intestinal anaerobic bacteria which are able to occur bacteremia or septicemia. So amplification of the 16srRNA and narG genes in this type of bacteria is the best way for detection of them and followed by the treatment of the patients. Results: 100 patients with septic arthritis incidences were studied here. From these numbers 61% were bacterial arthritis and 18% were infected by anaerobic bacteria. Conclusion: On the base of coding of nitrate reductase, the positive samples were identified Enterobacter cloacae and Methylovorus sp. O157 Escherichia coli and Borrelia garinii.